1990
DOI: 10.1128/jcm.28.4.689-693.1990
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and chemical characterization of pink-pigmented oxidative bacteria

Abstract: The biochemical and chemical characteristics were determined for 156 clinical isolates of pink-pigmented bacteria that are similar to but distinct from Methylobacterium extorquens (synonymous with Pseudomonas mesophilica). These isolates were gram-negative, nonfermentative, usually nonvacuolated, coccoid rods; all grew at 35 degrees C and were catalase and urease positive; the majority grew on MacConkey agar and were variable for oxidase production and motility. On the basis of oxidation of xylose and mannitol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Many belonging to these groups are unusual opportunistic pathogens that may grow slowly and need to be distinguished from traditional fastidious pathogens. In characterizing a collection of strains that resembled Methylobacterium extorquens, Wallace et al (159) relied heavily on CFA composition to define groups with similarities and groups with differences. CFA analysis may reveal differences not readily apparent by phenotypic characterization.…”
Section: Mycoplasmas and Virusesmentioning
confidence: 99%
“…Many belonging to these groups are unusual opportunistic pathogens that may grow slowly and need to be distinguished from traditional fastidious pathogens. In characterizing a collection of strains that resembled Methylobacterium extorquens, Wallace et al (159) relied heavily on CFA composition to define groups with similarities and groups with differences. CFA analysis may reveal differences not readily apparent by phenotypic characterization.…”
Section: Mycoplasmas and Virusesmentioning
confidence: 99%
“…Finally, to 104 characterize lipidomic adaptation at varying cell densities, cells were harvested at early, mid and late 105 exponential, as well as stationary growth stages (Figure 1b). Cellular lipid content was analyzed by 106 high resolution shotgun mass spectrometry (Ejsing et al, 2009) It has been previously shown that M. extorquens produces lipids with 16 and 18 carbon atoms-long 111 acyl chains, and with up to 2 double bonds per acyl chain (Bradley et al, 2017;Wallace et al, 1990). 112…”
Section: Introduction 33mentioning
confidence: 99%
“…The strain was able to oxidize methanol (growth on oxidative-fermentative basal medium [Merck, Darmstadt, Germany]) supplemented with 1% methanol under aerobic conditions), was oxidative, and gave positive catalase, oxidase, and urease reactions (API 20 NE, bioMeriéux, Nürtingen, Germany). Oxidation of methanol is characteristic of members of the genus Methylobacterium and allowed differentiation from bacteria belonging to the closely related genus Roseomonas (7,(12)(13)(14). Further criteria to distinguish the strain isolated in this study from the genus Roseomonas were Gram-stain morphology and failure to grow on MacConkey agar (12)(13)(14).…”
mentioning
confidence: 99%
“…Oxidation of methanol is characteristic of members of the genus Methylobacterium and allowed differentiation from bacteria belonging to the closely related genus Roseomonas (7,(12)(13)(14). Further criteria to distinguish the strain isolated in this study from the genus Roseomonas were Gram-stain morphology and failure to grow on MacConkey agar (12)(13)(14). The biochemical characteristics of diagnostic importance of the isolated strain are summarized in Table 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation